Synthesis and Characterization of Al-TiO2/ZnO and Fe-TiO2/ZnO Photocatalyst and Their Photocatalytic Behaviour - Moradi, Shahram; Aberoomand Azar, Parviz; Raeis-Farshid, Sanaz; Abedini-Khorrami, Saeed; Hadi Givianrad, Mohammad (Asian Journal of Chemistry, 2013)
The TiO2/ZnO, Al-TiO2/ZnO and Fe-TiO2/ZnO nanocomposites as photocatalysts were prepared by the sol-gel method. The structures and properties were recognized with fourier transform infrared spectroscopy, scanning electron microscopy and X-ray diffraction methods. The XRD studies showed that addition of aluminum and iron to TiO2/ZnO affected on the particle size of nanocomposite. UV-visible spectrophotometry was used to determine dye concentration. The photocatalytic activity of the synthesized nanocomposites was investigated for decolorization of methyl orange and methylene blue in water under UV irradiation in a batch reactor. The results revealed that the photocatalytic activity of the nanocomposites for decolorization of methylene blue was better than methyl orange.